Study of Maternal and Fetal Outcome in Pregnancy with Heart Disease (Anwer Khan Modern Medical College Journal, 2017)
Background: Heart disease complicating pregnancy is an important indirect cause of maternal mortality and morbidity. Maternal heart disease comprises .2%-2% of pregnancies and responsible for 10%-20% of maternal deaths1. Our study was done to evaluate fetomaternal outcomes in pregnancy with heart disease.Objectives: Evaluation of fetomaternal outcome in pregnant patients with cardiac disease. Materials andMethods: This observational study was done in Bangabandhu Sheikh Mujib Medical University and Anwer Khan Modern Medical College Hospital among 51 pregnant women with known or newly diagnosed heart disease from January 2013-january 2015. Baseline data recorded demographic character, NYHA functional class, maternal complications, mode of delivery and neonatal outcome.Results: Among 51 cardiac patients, 32 (63%) were primigravida. Mostly 46 (90.6%) belonging to NYHA Class I and II. Rheumatic heart disease seen in 45 (87%) and congenital heart disease in 10% subjects. Mitral stenosis was the most common, seen in 22 (41%) cases. 47.33% patients were delivered vaginally and LSCS done in 41% patients. The fetal outcome were live births in (96.6%) cases, (27.4%) babies required NICU admission.Conclusion: An improvement in modern techniques of monitoring, better understanding of pathophysiology of cardiac disease and multi disciplinary care can lead to substantial improvement in the feto maternal outcome.Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 112-116